Assessment of maturity of reverse logistics as a strategy to sustainable solid waste management (2020)
Small- and medium-sized enterprises primarily focus on their operations and rarely pay attention to issues related to sustainable solid waste management that originate from their production processes. A suitable strategy to support sustainable solid waste management is reverse logistics. Through the use of maturity models, it is possible to determine the grade to which small- and medium-sized enterprises are prepared to perform this strategy. This study proposes an adapted maturity model to measure maturity levels of reverse logistics aspects at small- and medium-sized enterprises in regions from Colombia in order to contribute to sustainable solid waste management. The maturity model was applied to seven small- and medium-sized enterprises in the plastics sector in the central and southern regions of Colombia by adapting a maturity model that was previously correlated to suggested drivers and barriers in this sector. Results show that maturity levels range from naïve to immature owing to the incipient development of reverse logistics in Colombia. Therefore, it is necessary to establish a holistic vision of the organisation to improve the reverse logistics decision-making process to achieve sustainable solid waste management